Adherence to Infliximab Treatment in a Pediatric Inflammatory Bowel Disease Cohort. Issue 4 (October 2015) - Vitale, David S.; Greenley, Rachel N.; Lerner, Diana G.; Mavis, Alisha M.; Werlin, Steven L.
<x xml:space="preserve">Abstract</x> Abstract The aims of the study were to describe infliximab adherence in a pediatric inflammatory bowel disease cohort, to identify demographic and disease factors associated with adherence, and to examine differences in acute care use among adherent and nonadherent patients. Charts of patients who received infliximab at the Children's Hospital of Wisconsin (CHW) between October 2010 and October 2012 were retrospectively reviewed. A total of 151 patients met the inclusion criteria; 91.4% of the patients were adherent. Nonadherent patients had more emergency room visits and hospitalizations than adherent patients. The study is the first to show high adherence rates to infliximab in a pediatric cohort.